Wong Kar-Wai: Interviews - Lee, Micky and Lee, Silver Wai (University Press of Mississippi, 2018)
Fans and critics alike perceive Wong Kar-wai (b. 1958) as an enigma. His dark glasses, his nonlinear narrations, and his high expectations for actors all contribute to an assumption that he only makes art for a few highbrow critics. However, Wong's interviews show this Hong Kong auteur is candid about the art of filmmaking, even surprising his interlocutors by suggesting his films are commercial and made for a popular audience. -- -- Wong's achievements nevertheless feel like art-house cinema. His third film, Chungking Express, introduced him to a global audience captivated by the quick and quirky editing style. His Cannes award-winning films Happy Together and In the Mood for Love confirmed an audience beyond the greater Chinese market. His latest film, The Grandmaster, depicts the life of a kung fu master by breaking away from the martial arts genre. In each of these films, Wong Kar-wai's signature style-experimental, emotive, character-driven, and timeless-remains apparent throughout. -- -- This volume includes interviews that appear in English for the first time, including some that appeared in Hong Kong magazines now out of print. The interviews cover every feature film from Wong's debut As Tears Go By to his 2013 The Grandmaster.
https://katalog.adlr.link/Record/51-9781496820259